PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA INDUSTRI JASA NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Margaretha, Farah; Afriyanti, Evi (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2016)
The aims of this research is analyze the effect ofcorporate governance to firm performance of non financial services industry listed in Indonesia Stock Exchange. The sample used as many 37 companies period 2010-2014. The dependent variable in this research is the firm performance is measured by Return on Assets (ROA), while the independent variable are ownership concentration, managerial ownership, board size, CEO family, agency costs (asset turnover and expense ratio), firm size and leverage (long term debt to total assets and long term debt to equity ratio). The analysis method used is multiple linear regression. The results show that there is a positive influence between the agency cost, firm size and leverage to firm performance, there is also negative influence between the agency costs and leverage to firm performance, and there is no influence between ownership concentration, managerial ownership, board size, CEO family to firm performance.